Bucólicas - Virgilio Marón, Publio; Recio García, Tomás de la Ascención; Vidal, José Luis (Madrid : Gredos, 2010)
Las Bucólicas -- Las Geórgicas -- La Eneida -- Melibeo Títiro -- Alexis -- Menalcas, Dametas, Palemón -- Polión -- Menalcas, Mopso -- Sileno -- Melibeo, Coridón, Tirsis -- Damón, Alfesibeo -- Lícidas, Meris -- Galo
Notas al pie de página
Audiencia general
Traducido del Latín al Español.
Keywords: Poesía Latina